Meck Dialect and it’s Function in Contributing Language Variation on the Students of Yahukimo Communities at Merauke - Nasrawati; Manson Uuk (Jurnal Ragam Pengabdian, 2026)
This research discussed about Meck dialect and its function in contributing language variation on the students of Yahukimo community at Merauke. This research applied descriptive qualitative method in revealing the data by using interviews and recordings to the 22 students of Yahukimo community at Merauke. This research found out that the Meck dialect contributing the language variation trough it functions in the society. There were three functions of Meck dialect was found namely cultural identity, group communication, and social marker. There were about 27 words of Meck dialect which was analyzed as the function of the language and it contribute the language variation of the Yahukimo community at Merauke. This research confirms the importance of documenting and revitalizing the Meck dialect in increasingly knowledge of sociolinguistic and to maintain cultural heritage sustainability amid globalization's challenges.